ENGINEERING THE ASCENDED ANTHROPOCENE: QUANDARIES OF BIOAUGMENTATION IN SELECT TEXTS - Anoop. P. K.; Anupama S S (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This paper examines the transformative potential of biotechnologies, artificial intelligence (AI), and performance optimization techniques in shaping the "Ascended Anthropocene man." It explores the ethical dilemmas and societal ramifications of human augmentation, emphasizing the necessity for a structured and responsible framework. By integrating insights from neuroscience, bioengineering, speculative fiction, and ethical studies, this study proposes a multidimensional framework for augmentation governance. The framework encompasses key principles such as ethical safeguards, equitable access, and regulatory oversight, ensuring sustainable and inclusive enhancement. Drawing upon chaos theory and sociotechnical analysis, this research highlights how small technological shifts can lead to unpredictable systemic consequences. Through case studies—including Apex, Redesigning Humans, and contemporary biohacking practices—this paper demonstrates how augmentation can reshape identity, cognition, and social structures. Ultimately, it advocates for a balanced augmentation paradigm that prioritizes both human potential and ethical responsibility in the Anthropocene era.